Spinocerebellar ataxia type 14 (SCA14) in an Argentinian family: A case report - Duggirala, Niharika (2023)
Background Hereditary spinocerebellar ataxias are a group of genetic neurological disorders that result in degeneration of the cerebellum and brainstem, leading to difculty in controlling balance and muscle coordination. Case presentation A family afected by spinocerebellar ataxia was identifed in Argentina and investigated using whole exome sequencing to determine the genetic etiology. The proband, a female white Hispanic aged 48, was noted to have slowly progressive gait ataxia, dysarthria, nystagmus, and moderate cerebellar atrophy. Whole exome sequencing was performed on three afected and two unafected family members and revealed a dominant pathogenic variant, p.Gln127Arg (19:54392986 A>G), in the protein kinase C gamma gene, and the family was diagnosed with spinocerebellar ataxia type 14. Conclusions To our knowledge, no previous cases of spinocerebellar ataxia type 14 have been reported in Argentina, expanding the global presence of this neurological disorder. This diagnosis supports whole exome sequencing as a high-yield method for identifying coding variants causing cerebellar ataxias and emphasizes the importance of broadening the clinical availability of whole exome sequencing for undiagnosed patients and families.